Roles of selected genetic variations and molecular alterations and molecular alterations in human papillomavirus-mediated cancer of uterine cervix - Cheng, Tan Shing (2016)
Although human papillomavirus (HPV) is essential for cervical carcinogenesis, it alone is insufficient to result in the malignant transformation of the cervix. Information on the roles of selected genetic variations as well as molecular alterations (in the forms of gene expression, DNA copy number alterations and loss of heterozygosity) in cervical cancer is currently lacking among Malaysian women. The present study was therefore undertaken to fill this gap of the literature. For this purpose, the associations of 12 genetic polymorphisms in nine candidate genes involved in various carcinogenic pathways with cervical cancer risk were evaluated on 185 histopathologically confirmed cervical cancer patients and 209 cancer-free female controls. The mRNA expression levels of these nine candidate genes, as well as the genome-wide copy number alterations and allelic imbalances were also analyzed in cancerous and non-cancerous tissues of 72 of the subjects. All data obtained were subsequently stratified by ethnicity and HPV subtypes involved. In addition, data on tumor molecular alterations was also stratified by stages and histopathology of the cancer. Besides, the association between the genetic polymorphisms and their respective gene expression levels was investigated. It was demonstrated that 154 (83.2%) of the cervical cancer patients and none (0.0%) of the cancer-free female controls were positive for HPV infection. Among the HPVpositive subjects, 141 (91.6%) had single-type HPV infections (of which HPV16, HPV18 and HPV58 predominated), while the remaining 13 (8.4%) were simultaneously infected by two HPV types (with HPV16 + HPV18 being the most common multipletype infection). It was also observed in the present study that after adjustment to known risk factors of cervical cancer, TNF c.-488G>A, CTLA4 c.49A>G, FAS c.-671A>G, MDM2 c.14+309T>G and CCND1 c.723G>A polymorphisms showed statistically significant associations with the risk of the cancer when analyzed singly. In addition, statistically significant observations were noted for the several combinations of CTLA4 c.-319C>T polymorphism with TNF c.-418G>A, CDKN1A c.93C>A and CCND1 c.*687C>G polymorphisms. Apart from that, it was shown in the present study that PUM1, YWHAZ and RPLP0 were the most stably expressed reference genes in cervical cancer, and normalization of expression levels of the nine candidate genes against these reference genes showed no significant relative expression difference between cancerous and non-cancerous tissues of the cervix. However, an association was found between a higher CTLA4 expression and the variant allele of CTLA4 c.49A>G polymorphism, and between a lower FAS gene expression and the variant allele of FAS c.-671A>G polymorphism. The present study also successfully characterized the landscape of genome-wide copy number alterations and loss of heterozygosity in cervical cancer tissues, and observed that the most common loci with recurrent genomic alterations were 3q21.3, 10q26.3 and 5p15.33 (for copy number gains), 11p11.12, Xp11.1 and 12q11 (for copy number losses), and Xq11.1, Xq22.3 and 16p11.2 (for losses of heterozygosity). In conclusion, the present study has successfully determined the prevalence and distribution of HPV types among Malaysian women, identified several host genetic polymorphisms associated with risk of cervical cancer, and identified some major molecular alterations which occurred in the cancerous and non-cancerous tissues of cervical cancer patients. These results have a potential prospect in the promising field of individualized preventive medicine.